2023
DOI: 10.1186/s12967-023-04249-6
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of extracellular vesicle-delivered miR-185-5p in the plasma of patients as an indicator for advanced adenoma and colorectal cancer

Abstract: Background We aimed to evaluate whether extracellular vesicles (EV)-derived microRNAs (miRNAs) can be used as biomarkers for advanced adenoma (AA) and colorectal cancer (CRC). Methods We detected the changes in the plasma EV-delivered miRNA profiles in healthy donor (HD), AA patient, and I-II stage CRC patient groups using miRNA deep sequencing assay. We performed the TaqMan miRNA assay using 173 plasma samples (two independent cohorts) from HDs, A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous research has shown different results on the influence of miR-185-5p on cancer advancement, with contradictory functions observed as both inhibiting and promoting tumor growth (Scognamiglio et al 2022 ; Değerli et al 2020 ; Yu et al 2022 ). A recent research discovered that miR-185-5p delivered through extracellular vesicles in the blood of individuals can serve as a marker for advanced adenoma and colorectal cancer (Shi et al 2023 ). In the field of PDAC research, it has been highlighted that miR-185-5p exerts regulatory control over non-protein coding RNA, thereby fostering the progression of pancreatic cancer (Li et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown different results on the influence of miR-185-5p on cancer advancement, with contradictory functions observed as both inhibiting and promoting tumor growth (Scognamiglio et al 2022 ; Değerli et al 2020 ; Yu et al 2022 ). A recent research discovered that miR-185-5p delivered through extracellular vesicles in the blood of individuals can serve as a marker for advanced adenoma and colorectal cancer (Shi et al 2023 ). In the field of PDAC research, it has been highlighted that miR-185-5p exerts regulatory control over non-protein coding RNA, thereby fostering the progression of pancreatic cancer (Li et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVs are secreted from almost all cell types, act as mediators of intracellular communication and are considered early biomarkers of disease [ 48 ]. They may even participate in immunomodulatory oncogenic processes, reshape immune function, and are early indicators of cancer-associated thrombosis [ [49] , [50] , [51] ]. Here, we studied EVs at the experimental endpoint with a focus on immune modulation and coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence reveals that non-coding RNA overexpression or depletion accelerates CRC development and growth, representing potential molecular prognostic and therapeutic biomarkers [8]. Indeed, aberrant expression of several miR-NAs, including miR-21, miR-146b, miR-342-3p, miR-185-5p, miR-675-5p, miR-128-1-5p, miR-138-5p, and miR-451, is frequently found in CRC [9][10][11][12][13][14][15][16]. Moreover, the miR-148a-3p gene, located on the 7p15.2 region of human chromosomes, also plays a critical role in the carcinogenesis and progression of many cancer types, including CRC [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%